Construction of quasi-cyclic LDPC codes form SFT structure and cyclic shift - Timakul, Sekson; Choomchuay, Somsak (My University, 2011)
This paper presents an alternative a method for designing a parity matrix of low density parity check codes. The proposed method can be viewed as a generalized version of Sridara-Fuja-Tanner (SFT) technique which is ideal for regular quasi cyclic code design. Upon the current investigation, the designed code has delivered a comparable BER-SNR performance when compared with that of more complicate designed matrix. The designed code offers similar performance when compared with Sridara-Fuja-Tanner code and Quadratic Congruences structure. In additions, the resulted matrix also has a desirable structure that it suits well the hardware implementation. © 2011 IEEE.
Keywords: LDPC codes; quasi-cyclic (QC) codes